2014
DOI: 10.4172/2155-6113.1000302
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cells Coordinate with Th22 Cells in Maintaining Homeostasis of Intestinal Tissues and both are Depleted in SIV-Infected Macaques

Abstract: Th17 and Th22 cells are thought to function as innate regulators of mucosal antimicrobial responses, tissue inflammation and mucosal integrity, yet their role in persistent SIV infection is still unclear. Here we compared Th17 and Th22 cells in their phenotype, effector/cytokine function, and frequency in blood and intestinal mucosal tissues, and correlate levels with mucosal damage in SIV-infected rhesus macaques. We found that Th17/Th22 cells share similar features in that both highly produce TNF-α and IL-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…In the intestinal mucosa, ILC3 cells are in close proximity to the epithelial barrier and are likely among the first cells to encounter microbial products once the epithelial barrier is compromised. Although direct evidence showing that the loss of ILC3 correlates with intestinal mucosal damage in SIV-infected rhesus macaques is lacking, studies in mice suggest that once ILC3 cells are lost, the integrity and innate immunity of mucosal tissues will be further compromised (18,46,47), and our data showed that ILC3 cells positively correlated with intestinal T h 22 cells, which are closely associated with mucosal integrity (40,48). Therefore, preservation or restoration of ILC3 cells during HIV infection may facilitate restoration of lymphoid tissues, and both innate and adaptive immune responses, and mitigate microbial translocation and the systemic immune activation that leads to disease progression in SIV/HIV (49).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In the intestinal mucosa, ILC3 cells are in close proximity to the epithelial barrier and are likely among the first cells to encounter microbial products once the epithelial barrier is compromised. Although direct evidence showing that the loss of ILC3 correlates with intestinal mucosal damage in SIV-infected rhesus macaques is lacking, studies in mice suggest that once ILC3 cells are lost, the integrity and innate immunity of mucosal tissues will be further compromised (18,46,47), and our data showed that ILC3 cells positively correlated with intestinal T h 22 cells, which are closely associated with mucosal integrity (40,48). Therefore, preservation or restoration of ILC3 cells during HIV infection may facilitate restoration of lymphoid tissues, and both innate and adaptive immune responses, and mitigate microbial translocation and the systemic immune activation that leads to disease progression in SIV/HIV (49).…”
Section: Discussionmentioning
confidence: 49%
“…3). The loss of T h 17 and T h 22 cells has been correlated with the breakdown of mucosal integrity, microbial translocation, and chronic immune activation (22,40,41). Because ILC3 cells play critical roles in formation of lymphoid tissue, adaptive immunity, regulation of mucosal microbiota via AhR, restoration of secondary lymphoid tissues after injury, and maintenance of intestinal memory CD4 T cells (3,17,18,45), their losses undoubtedly contribute to compromised mucosal immunity in HIV infection and AIDS, including failure of humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells have been identified as being highly susceptible in vitro and selectively depleted from the gut and FRT (Canary et al, 2013; Klatt et al, 2012; Xu et al, 2012; Xu et al, 2014). We hypothesized that the virus would also preferentially target these cells during transmission.…”
Section: Resultsmentioning
confidence: 99%
“…ICS staining for IL-17 was included in the present study since perturbations in CD4 + and CD8 + IL-17-staining cells in both the periphery and mucosal compartments reportedly reflect SIV-induced changes in disease status [3436] and therefore could be a useful marker particularly in animals that may become dually-infected after challenge with virulent virus ( i . e .…”
Section: Discussionmentioning
confidence: 99%